Psychiatric and substance abuse comorbidity among HIV seropositive and HIV seronegative prisoners in Malaysia - Zahari, M.M.; Bae, W.H.; Zainal, N.Z.; Habil, H.; Kamarulzaman, A.; Altice, F.L. (2010)
Objective: To examine the association between HIV infection and psychiatric disorders among prisoners, where mental illness, substance abuse, and HIV are disproportionately represented. Design: Cross-sectional study. Methods: Using a sequential randomization scheme, 200 HIV-seropositive and 200 HIV-seronegative prisoners were selected for evaluation of psychiatric illnesses with the Structured Clinical Interview for Diagnostic Statistical Manual of Mental Disorders-IV (SCID-I). Results: The prevalence of mental illness and substance use disorders, particularly opioid dependence, was extremely high. HIV infection was significantly correlated with age, ethnicity, marital status, history of injection drug use, lifetime duration of incarceration, substance abuse, and polysubstance drug use. After controlling for potential confounders, HIV infection was significantly associated with non-substance-induced psychiatric disorders (AOR = 1.92; 95 CI: 1.03-3.59). While prisoners with a triple diagnosis (psychiatric disorders, substance use disorders, and HIV) spent 46.7 more cumulative lifetime months in prison than those with only a psychiatric diagnosis (p<.01), those with a dual diagnosis (psychiatric plus substance use disorders) were comparable to those with one psychiatric diagnosis only. Neither HIV infection nor triple diagnosis was associated with violent offenses. Conclusion: These findings suggest that a public health approach that simultaneously addresses psychiatric illnesses, substance abuse, and HIV infection is needed in both the correctional and the community settings in order to provide adequate care for triply-diagnosed patients and prevent them from returning to prison.